Perceptions and use of question types by TEFL teachers in Oman: a pedagogical study - Moosa Ahmed; Suyansah Swanto; Wardatul Akmam Din (EuroJournals, Inc., 2015)
With this premise as a backdrop that effective use of questions in instructional practices is of vital importance in EFL classrooms, this study was undertaken to investigate teachers' perceived knowledge and their actual use of question types in grades 5-12 in Omani schools with reference to cognitive questions, affective questions, display questions, referential questions, and interactional modifications. The present study made an attempt to look for differences among teachers in using questions based on their gender, nationality, and grade level. A total of 120 EFL teachers representing a percentage of 40% of the total population of all EFL male and female teachers in Dhofar region of Oman participated in this study. Data analysis showed that EFL teachers in Oman claim that they are highly knowledgeable about the use of different question types. However, the correlation between teachers' perceived knowledge with their actual use of question types varied according to the question type. Results also indicate that there are no significant differences regarding gender, nationality, and grade level in the use of question types. In view of the discussion of findings pedagogical implications are explored and recommendations made.